Development of Google Sites Website-Based Learning Media for Local History Material in Class XI SMA N 1 Tanjung Raja - Yessi Lestari; Sani Safitri (UNDIKMA, 2023)
Through the internet, learners can access the necessary information including science as needed. However, this is not accompanied by the clarity, validity of the sources on internet sites which sometimes do not provide complete information and even confuse the students. The aim of this research is to develop a product in the form of a google sites website containing material on the Japanese Occupation Period in Palembang class XI SMA Negeri 1 Tanjung Raja that is both valid and effective. The development was carried out using the Rowntree model which consisted of three steps, planning, development and evaluation. This evaluation was carried out using the Tessmer evaluation method which includes self evaluation, expert review, a one-to-one evaluation and a small group evaluation. The score obtained after validation on experts, namely material experts with 4.77 scores (very valid), media experts with 3.90 scores (valid), item test experts 4.44 (very valid) and grammar experts with 3.88 scores (valid). This research and development has produces the google sites product website where at the one to one stage it gets a score of 4.51 very valid categories, small groups get a score of 4.35 very valid categories. After the learning process with the product that has been developed, there is a percentage, which is an improvement in learning results of 52.4%, an increase in success of 84, 55% and n gain obtained of 0.78 in the category of high. Thus, produces the google sites product website on local history material of the Japanese Occupation Period in Palembang is feasible to use and has a potential impact in learning history.